(untitled) - Đặng, Duy Lợi; Đào, Ngọc Hùng (H., 2016)
Tài liệu tham khảo tr. 672-676
Keywords: Biến đổi khí hậu -- Đặc điểm -- Nguyên nhân; Biến đổi khí hậu -- Tác động -- Ứng phó; Biến đổi khí hậu -- Giáo dục